Self-regulating behavior of hybrid membrane systems as demonstrated in an element-scale forward osmosis-reverse osmosis hybrid system - Ferguson, Noah; Chowdhury, Maqsud; Fitzsimonds, Colin; Beauregard, Nicole; Ostwal, Mayur; Pemberton, Marianne; Wazer, Edward; Cyr, Caylin; Srivastava, Ranjan; McCutcheon, Jeffrey R. (Journal of Membrane Science Letters, 2025)
•Hybrid membrane systems require flow balancing between unit operations.•Unbalanced flow between unit operation can starve or overflow downstream processes.•Buffer tanks can offer operational flexibility.•Forward osmosis hybridized with reverse osmosis with a buffer tank can self-regulate.•Leveraging thermodynamic equilibrium tendencies can reduce control and design complexity. Hybrid membrane systems can be difficult to design due to the requisite flow rate matching between up- and downstream unit operations. In this work, we use a forward osmosis-reverse osmosis (FO-RO) hybrid system to demonstrate how some membrane systems can exhibit self-regulating behavior due to osmotic coupling. This can reduce the need for complex control systems for flow balancing. We show this behavior using a module-scale test bed that can mimic the behavior of larger scale operations. The system shows permeate flow rate near-convergence between the FO and RO modules after startup or when perturbed by a change in RO module pressure. The behavior of this hybrid system demonstrates that some membrane operations can exploit osmotic interdependence, rather than expensive control systems, to achieve steady state operation. [Display omitted]